Post-operative sonological evaluation of pelvi-ureteric drainage of unilateral A-H pyeloplasty in children - Islam, Md Shakhawat; Amin, Md Ruhul; Hossain, AKM Zahid; Siddiqui, Md Tosaddeque Hossain; Islam, KM Didarul; Mondal, Susankar Kumar; Nooruzzaman, Md; Akan, Md Abu Bakar; Nazlee, Farah (Bangabandhu Sheikh Mujib Medical University Journal, 2023)
Background: Pelvi-ureteric junction obstruction is the most common cause of pediatric hydronephrosis where A-H pyeloplasty with D-J stent is the established treatment option with a high success rate. We observed the predictive value of sonological parameters for early detection of postoperative obstruction at the new pelvi-ureteric junction in children following unilateral A-H pyeloplasty. Methods: This cross-sectional study included 12 children who underwent unilateral A-H pyeloplasty. Post-operative follow-up was done after D-J stent removal and completed within six months. Maximum antero-posterior pelvic diameter (APPD), cortical thickness (CT), and pelvi-cortical (P/C) ratio were compared. Results: Mean APPD was 32.7 mm at the day after removal of the stent, 24.4 mm at one month, and 19.7 mm at four months. Mean CT was 5.2 mm at the day after removal of the stent, 6.1 mm at one month and 8.0 mm at four months. P/C ratio was 8.3 mm at the day after removal of the stent, 5.2 mm at one month, and 3.4 mm at four months. Increased CT and reduced P/C ratio were significant at four months (P= 0.05). Conclusion: CT value and P/C ratio can be used as an early marker of success for pelvi-ureteric drainage following A-H pyeloplasty.